The energy conversion efficiency of driver shot in female professional and amateur golfers - Hashimoto, H.; Nozawa, M.; Yoshioka, S.; Otsuka, M.; Isaka, T. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to evaluate the performance of driver shot from the viewpoint of the energy conversion efficiency between club head and ball at impact. Six female professional golfers and six female amateur golfers participated in this study. All subjects were instructed to hit a straight ball with their usual swing. Each subject performed ten trials. Three dimensional coordinates of reflective markers attached on a body and club landmarks were obtained using the motion capture system operating at 250 Hz. High speed camera was used to measure the movement of the club head and ball. The energy conversion efficiency was significantly different between professional and amateur golfers (p<0.01). This result suggests that not only club head speed but also the energy conversion efficiency are important for driving distance.